Falling Detection based on the Internet of Things - Lian, Zihao (International Journal of Computer Science and Information Technology, 2024)
This article proposes a method for fall detection through computer vision. With the increasing aging population in China, falling has become a major form of hazard to the safety of the elderly. This method aims to utilize computer vision to detect and record falling behaviors. This article has designed a detection method using YOLOV5 as a tool. Compared to traditional detection methods, YOLO offers faster detection speed and more accurate detection accuracy, which will greatly enhance the speed of discovering falls among the elderly and facilitate timely rescue efforts.